(untitled) (Altre Modernità, 2016)
Our contribution takes into consideration the more significant aspects of the student movement in Chile since 2001, year of the so-called mochilazo, up to nowadays, adopting a perspective aimed to outline the features of a historic process still in progress and in continuous transformation. Special attention is paid to the so-called revolucion de los pinginos and, above all, to the university student movement of 2011, which has been considered by many Chilean sociologists as a new social movement, to be deemed similar to the ones arisen during the recent past also in Europe, that represented the awakening of the civil society in front of the official political affairs. In this respect the relevant bibliography largely refers to Chilean works and is quite disparate, since it consists of documentary texts (investigative reports, memoirs of the protagonists, interviews) as well as historical texts, as the Historia contemporànea de Chile written by Gabriel Salazar and Julio Pinto (2014) and the sociological analysis of Mario Garcés (2012) and of Manuel A. Garretón (2014).